Atlas for the Territorial Agenda 2030. Maps on European territorial development. - (:unkn) unknown (My University, 2020)
A new atlas of the Federal Ministry of the Interior, Building and Community illustrates the development of the regions in Europe. Maps, figures and short texts show how the regions differ, where they are similar and what challenges they are facing – for example in the areas of economy, demography, labour market, education, research and the environment. The Federal Institute for Research on Building, Urban Affairs and Spatial Development (BBSR) and the European regional research network ESPON have developed the map collection for the German Federal Ministry of the Interior. The atlas was created during the German EU Council Presidency. It refers to the TA 2030. The 49 thematic maps and 32 illustrations of the atlas take up the focuses – a green and just Europe. The atlas addresses actors who want to deal with regional development issues in Europe. The BBSR and ESPON have evaluated official data from national statistical offices and other data sources for the atlas. Depending on the topic, the figures refer to different territorial units such as municipalities and regions.
Keywords: Raumentwicklung; Regionalentwicklung; Kartenwerk; Planungsatlas; Kartierung; Themakarte; Europäisches Raumentwicklungskonzept; Territoriale Agenda 2030